Konsep Iddah Bermasuk Masukan Menurut Kitabun Nikah Dan Mugni Al-Muhtaaj - Pambudi, Bagus; Riah, Juai; Hafizah, Nurul; Hafidzi, Anwar (Sharia Journal and Education Center Publishing, 2024)
Abstract This research analyzes the concept of iddah entry in the work of Sheikh Muhammad Arsyad al-Banjari Kitabun Nikah, Rujuk is an alternative in Islamic law as a solution for couples who have divorced. Sheikh Muhammad Arsyad al-Banjari believes that husband reconciliation is invalid without words, which is classified as one of the conditions for reconciliation in the